Voltage unbalance compensation in islanded microgrid system by using negative sequence current feedback - Fu, Qihao (2017)
Power quality control still remains as one of major research topic in power engineering. Weak power quality affects the reliability and efficiency of the utility and consumers. One of the contributing factors is voltage unbalance which could potentially affects sensitive equipment such as electronics and induction motors. With the use of hierarchical control having primary and secondary control, this paper will introduce the use of voltage unbalance compensation and negative sequence current feedback in an islanded microgrid to improve overall power quality. With the installation of proportional integral (PI) controllers in each individual Distributed generator (DG), it is able to exchange data with its neighbouring DGs. A total of 3 DGs will be connected to the point of common coupling (PCC) in parallel with simulation of unbalanced loads using MATLAB.